Determination of Rutin from Ginkgo biloba L. Leaves by Ultrasound-Assisted Extraction with Natural Deep Eutectic Solvent-Based Cellulose Polymers and High-Performance Liquid Chromatography (HPLC). (4th March 2022) - Dai, Yunliang; Row, Kyung Ho
Abstract: Rutin from Ginkgo biloba L . leaves (78.63 mg g −1 ) was mildly and effectively extracted using an ultrasound-assisted process with tailor-designed natural deep eutectic solvent-based cellulose polymer adsorbents. The physicochemical properties and structural characteristics of the synthesized natural deep eutectic solvent-modified cellulose polymers were examined by Fourier transform infrared spectroscopy, field emission scanning electron microscopy, thermogravimetric analysis, and elemental analysis. The ultrasound-assisted extraction conditions were optimized using a response surface methodology (extraction time, 40 min; sample to solvent ratio, 1:29 g/mL; extraction temperature, 81 °C; and ultrasound frequency, 180 W). The ultrasound-assisted extraction method is environmentally friendly and allows the simple and easy recovery of components. In addition, this approach is effective for the extraction, separation, and detection of rutin. These findings might promote the applications of rutin from G. biloba L. leaves in several fields.